Academic Senate Minutes 2021-08-26 - Academic Senate:::::::::
Agenda approved. Minutes of 5/1 and 6/10 approved. Chair Report. President Report. Provost Report. Statewide Senator Report. Structure and Functions Report. Vice President of Administration and Finance Report. Vice President of Student Affairs Report. Re-assigning APC business. Possible Revisions to the Online and/or Hybrid Instruction Policy referred to EPC. Interim Certificate Approval Process – EPC approval supported. GMC report at the Senate – Results of summer retreat added to Senate agenda. Charge to Senate Budget Subcommittee. Faculty Involvement in Honorary Degree Program. New parliamentarian for the Senate – S. Brannen appointed as backup. EPC Report. FSAC Report. SAC Report. CFA Report. Associated Students Report. Senate agenda approved.